Radioactive games? Radiation hazard assessment of the Tokyo Olympic Summer Games - Querfeld, R.; Hori, M.; Weller, A.; Degering, D.; Shozugawa, K.; Steinhauser, G. (Environmental Science & Technology, 2020)
We conducted a comprehensive radiation hazard assessment of the Tokyo Olympic Games (Tokyo 2020, postponed to 2021). Our combined experimental and literature study focused on both external and internal exposure to ionizing radiation for athletes and visitors of the Games. The effective dose for a visit of 2 weeks ranges from 57 to 310 µSv (including flight dose). The main contributors to the dose are cosmic radiation during the flights (approx. 10-81 %), inhalation of natural radon (approx. 9-47 %), and external exposure (approx. 8-42 %). In this complex exposure, anthropogenic radionuclides from the Fukushima nuclear accident (2011) always play a minor role and have not caused a significant increase of the radiological risk compared to pre-Fukushima Japan. Significantly elevated air dose rates were not measured at any of the Tokyo Olympic venues. The average air dose rates at the Tokyo 2020 sites were below the average air dose rates at the sites of previous Olympic Games. The level of radiological safety of foods and water is very high in Japan, even for athletes with increased water and calorie demands, respectively.